PENGARUH POLA ASUH DAN LATAR BELAKANG PENDIIDKAN PRASEKOLAH TERHADAP KECERDASAN MAJEMUK REMAJA - Suherni, Heni; Hastuti, Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
Multiple intelligences essential for individual succeed. This study aimed to analyze the differences of multiple intelligences and caring practices of adolescents with the preschool educational background that were Preschool Group of Semai Benih Bangsa, kindergarten, and adolescents who didn’t have preschool education; analyzed the relationship among variables, and analyzed the variables that influence multiple intelligences in adolescents. The research was conducted in Situ Udik Village (Bogor Regency) and Sukamulya Village (Bogor City) by the number of participants were 91 adolescents. Data were collected through interviews and was analyzed using different test, correlation test, and regression test. Results showed that adolescents’ multiple intelligences among groups were significantly different. Multiple intelligences associated significantly with family income, family size, mother’s education, gender, caring practices, and the number of activities pursued by the adolescents. Variables that influenced adolescents’ multiple intelligences were mother’s education, the number of activities pursued by adolescents, and caring practices.